Primary proteolysis of white brined cheese prepared from raw cow milk monitored by high-molarity Tris buffer SDS-PAGE system - Milenko Smiljanić; Mirjana B. Pesic; Sladjana P. Stanojevic; Miroljub B. Barać (Mljekarstvo)
The aim of this work was to investigate primary proteolysis of white brined cow cheese prepared from raw milk by SDS-electrophoretic method based on high-molarity Tris buffer system and to correlate with the results of other commonly used parameters. Proteolytic changes of white brined cow cheese were monitored by three parameters: total protein, water soluble proteins and degree of proteolysis. Changes of major casein fractions were followed by SDS-electrophoretic system in reducing conditions. The total protein content and moisture content of white brined cow cheese were significantly affected by ripening. Ripening in brine increased water soluble proteins and degree of proteolysis. Major caseins were differently resistant to proteolysis; αs-CN was more susceptible than β-CN. The αs-CN content was highly and negatively correlated with time of ripening and water soluble proteins whereas no significant correlation (p<0.05) between β-CN content and these parameters was found. Also, a strong significant correlation (p<0.05) between the amount of low molecular weight products and time of ripening, water soluble proteins and αs-CN content was observed. SDS-PAGE method used in this study could be useful for monitoring the white cow cheese proteolysis.